3D Bioelectronic Interface: Capturing Circulating Tumor Cells onto Conducting Polymer‐Based Micro/Nanorod Arrays with Chemical and Topographical Control. Issue 15 (3rd April 2014) - Hsiao, Yu‐Sheng; Luo, Shyh‐Chyang; Hou, Shuang; Zhu, Bo; Sekine, Jun; Kuo, Chiung‐Wen; Chueh, Di‐Yen; Yu, Hsiao‐hua; Tseng, Hsian‐Rong; Chen, Peilin
<x xml:space="preserve">Abstract</x> The three‐dimensional (3D) poly(3, 4‐ethylenedioxythiophene) (PEDOT)‐based bioelectronic interfaces (BEIs) with diverse dimensional micro/nanorod array structures, varied surface chemical properties, high electrical conductivity, reversible chemical redox switching, and high optical transparency are used for capturing circulating tumor cells (CTCs). Such 3D PEDOT‐based BEIs can function as an efficient clinical diagonstic and therapeutic platform. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>